Effectiveness of Flipped Classroom Strategies on Learning Outcomes in Economics Threshold Concepts Across Arts, Commerce, and Science Disciplines in Secondary Schools - Abidat Mohammed; Akinola Jimoh; Samod Lawal-Arogundade (International Journal of Advanced Humanities Research)
The effectiveness of flipped classroom learning on learning outcomes in economics threshold concepts across three disciplines, namely arts, commerce, and science, in secondary schools in Nigeria was explored through a quasi-experimental design using a one-group pre-test and post-test format. A total of 12 schools were sampled using systematic sampling techniques from the four zones in Lagos State Education District V, with three schools from each of the zones that make up the district. Intact classes of year two senior secondary school students were used in each sampled school. The study tested three hypotheses at 0.05 level of significance. The results indicated that there was a significant joint influence of threshold concepts and flipped classroom strategies on learning outcomes in economics among senior secondary school students (F = 9.023, p < 0.05). No difference was seen in the learning outcomes among students from arts, commerce, and science disciplines (F = 0.66, p > 0.05). Hence, the results recommended that professional development on improved flipped classroom strategies needs to be given to economics teachers, as it has a significant positive effect on the learning outcomes.